Nilai Budaya Dalam Legenda Kapuas - Lastaria Lastaria (Jurnal Hadratul Madaniyah, 2017)
Cultural Values in the Legend Kapuas. Cultural values are the conception of ideal or ideal image of something that is seen and recognized precious lives in the mind; stored and embodied in the norms, rules, and laws; and articulated, unrevealed, and externalized in speech, action, action, and the behavior of most members of society as the unity and integrity. Of the eight legends Kapuas found some kind of cultural values, namely: (1) the amount of culture in the human relationship with the Lord, consisting of three cultural values which, thank god, like prayer, trust Kaharingan; (2) the cultural values of mankind's relationship with nature is a natural utilization of cultural values; (3) cultural values in human relationships with the community, there are three, namely consultation, cooperation, vigilance; (4) cultural values in human relationships with other human beings there are four, namely helpfulness, harmony, honesty, and sorry-forgive; and (5) the cultural values of mankind's relationship with itself, there are two, namely to try and strong-willed, self-confidence.